Technological Change, Relative Wages, and Unemployment - Aizenman, Joshua; Agenor, Pierre-Richard. (Washington, D.C. : International Monetary Fund, 1994)
This paper examines the effect of skill-biased technological change on the structure of wages, the composition of employment and the level of unemployment in a two-sector economy with a heterogenous work force. Efficiency wage considerations and minimum wage legislation lead to labor market segmentation. A technological shock that reduces the demand for unskilled labor and raises the demand for skilled labor in the primary, high-wage sector is shown to increase the relative wage of skilled workers and reduce aggregate employment as well as the employment level of unskilled workers in that sector. The net effect of the shock on the employment level of skilled workers is mitigated by the existence of efficiency factors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet